Does the Environment Matter for Poverty Reduction? : The Role of Soil Fertility and Vegetation Vigor in Poverty Reduction - Heger, Martin; Zens, Gregor; Bangalore, Mook (World Bank, Washington, DC, 2018)
The debate on the environment-poverty nexus is inconclusive, with past research unable to identify the causal dynamics. This paper uses a unique global panel data set that links (survey and census derived) poverty data to measures of environmental quality at the subnational level. The analysis uses vegetation vigor as a proxy for above-ground environmental quality and soil fertility as proxy for below-ground environmental quality. Rainfall is used to account for endogeneity issues in an instrumental variable approach. This is the first global study using quasi-experimental methods to uncover to what degree environmental quality matters for poverty reduction. The paper draws three main conclusions. (1) The environment matters for poverty reduction. The panel regression suggests that a 10 percent increase in vegetation vigor is associated with a poverty headcount ratio reduction of nearly 0.7 percentage point in rural areas, and 1 percentage point in Sub-Saharan Africa. A 10 percent increase in soil quality leads to a roughly 2 percentage point decrease in poverty rates in rural areas and in Sub-Saharan Africa. (2) The effects of environmental quality on poverty are stronger than its effects on average income, suggesting that the poor benefit disproportionately from environmental quality. (3) In situ environmental quality improvements are pro-poor, in contrast to urbanization. Although urbanization has highly significant and sizable correlations with GDP per capita, it is not significantly correlated with poverty reduction.